2015
DOI: 10.1111/iju.12867
|View full text |Cite
|
Sign up to set email alerts
|

Video‐urodynamic effects of mirabegron, a β3‐adrenoceptor agonist, in patients with low‐compliance bladder

Abstract: Abbreviations & Acronyms AA = anticholinergic agents BC = bladder compliance BoNT-A = botulinum toxin A CC = cystometric capacity CE = cleansing enema CIC = clean intermittent catheterization DO = detrusor overactivity Dx/HA = dextranomer hyaluronic acid copolymer injection for vesicoureteral reflux FDV = first desire to void JUH = Jikei University Hospital LUTD = lower urinary tract dysfunction OAB = overactive bladder P abd = abdominal pressure (cmH 2 O) P det = detrusor pressure P ves = intravesical pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…We determined that there was significant improvement in the volume at strong desire to void in both the mirabegron and tolterodine groups (Table ), which is similar to previous research . Increases in the cystometric capacity following mirabegron have been reported in women with OAB; in addition, similar findings in low compliance patients (three men and six women) and spinal cord injury patients, had been observed. The urodynamic findings of tolterodine are similar to previous reports …”
Section: Discussionsupporting
confidence: 86%
“…We determined that there was significant improvement in the volume at strong desire to void in both the mirabegron and tolterodine groups (Table ), which is similar to previous research . Increases in the cystometric capacity following mirabegron have been reported in women with OAB; in addition, similar findings in low compliance patients (three men and six women) and spinal cord injury patients, had been observed. The urodynamic findings of tolterodine are similar to previous reports …”
Section: Discussionsupporting
confidence: 86%
“…13 Other factors associated with better persistence with mirabegron were female patients, older aged patients or polypharmacy according to the previous studies. [21][22][23] Thus, better efficacy of combination therapy could result in a better persistence rate with mirabegron. Furthermore, the greater efficacy of combination therapy with mirabegron and antimuscarinics for OAB patients has already been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Mirabegron is considered a second line therapy to anticholinergics; however, there are still no recommendations for the combination therapy of anticholinergics and β3‐adrenoceptor agonists in any clinical guidelines . Recent clinical studies indicated that mirabegron for patients with neurogenic bladder dramatically improved bladder storage function and bladder deformity; however, there are few research studies to prove that mirabegron or the combination treatment are effective for neurogenic bladder dysfunction. In the present animals study, only the combination therapy of oxybutynin and mirabegron improved bladder compliance, ICI, voided volume, bladder capacity, and integral of NVCs compared to the vehicle therapy.…”
Section: Discussionmentioning
confidence: 99%